Coordination in Managing Earthquake Disaster Emergencies in North Tapanuli Regency in 2022 - Rikki Andika Hutahaean; Tunggul Sihombing (Jurnal Kebijakan Publik, 2025)
This research aims to identify and describe in detail the coordination in the emergency response to earthquake disasters in North Tapanuli Regency in 2022. The research method used in this study is a qualitative approach with a descriptive method. Data collection was carried out through interviews, observations, and documentation. The data obtained were analyzed qualitatively using the coordination theory proposed by Sugandha (1988:83-101) which includes: organizational structure, planning, procedures, and supervision. The results of the study indicate that the formation of the organizational structure and planning was coordinated effectively. However, procedures and supervision were not coordinated effectively. In the subvariable of organizational structure, the structure depicts important functions as part of the main tasks, the presence of unity of command, and a clear division of labor. In the subvariable of planning, the activity plans, implementation methods, and facilities used are well-coordinated. Furthermore, in the procedural implementation, the distribution of staple food aid to earthquake victims does not follow the procedure, as the distribution is not timely and inconsistent. In the subvariable of supervision, discrepancies are found between implementation and planning, where there are third parties providing direct assistance to victims; discrepancies between implementation and procedure, where the distribution of aid does not follow the correct procedures; discrepancies between implementation and objectives, in which the needs of the victims are not met evenly and not on time.